Evaluasi Compliance Risk Management (CRM) Dalam Kegiatan Pengawasan Di KPP Pratama Gianyar - Akhmad Shabarudin; Siti Nuryanah (LPMP Imperium, 2024)
The low number of Daftar Sasaran Prioritas Penggalian Potensi (DSP3) which derives from Compliance Risk Management (CRM) (8.47% of the DSP3) at Gianyar Tax Service Office motivates this study to evaluate the use of CRM called CRM Fungsi Pemeriksaan dan Pengawasan (CRM Rikwas) in supervision activities (starting from the planning, implementation, and follow-up stages) at Gianyar Tax Service Office. Evaluation is measured by the criteria of effectiveness at the planning stage of supervision and adequacy at the stage of implementation and follow-up stage of supervision. This study is a case study with an evaluation approach. The research method used is a qualitative method and descriptive analysis. Data was collected by collection of documentation, interviews with the Account Representative (AR) and the Head of the Supervision Section, and questionnaires to the AR. The results of the evaluation with the effectiveness criteria showed that CRM Rikwas suggests effectiveness in the planning stage of supervision. The results of the evaluation with the adequacy criteria indicate that the CRM Rikwas is not adequate in assisting the supervision activities (implementation and follow-up stages) because several indications of non-compliance are not following the actual situation. Based on these findings, this study recommends that AR at the Gianyar Tax Service Office review the non-conforming indicators first and recommends the DGT follow up on those findings.